The Role of Oxidation and Antioxidants in Miscarriage with the Impact of Polycystic Ovary Syndrome: Peran Oksidasi dan Antioksidan dalam Keguguran yang Berdampak pada Sindrom Ovarium Polikistik - Awad, Fayhaa Mohammed (Indonesian Journal on Health Science and Medicine, 2024)
This research explores the complex interrelationships between oxidative stress and its antagonists in the context of miscarriage. Miscarriage, a critical issue affecting women's health worldwide, results from various multifactorial causes including genetic, hormonal, immunological, and environmental factors. Notably, oxidative stress emerges as a pivotal element, exacerbating the risk and incidence of miscarriage through an imbalance between oxidants and antioxidants within the body. This imbalance leads to cellular damage that can compromise placental function and fetal development, thus influencing pregnancy outcomes. The study underscores the importance of antioxidants in mitigating oxidative stress, suggesting their potential therapeutic role in improving pregnancy outcomes and reducing miscarriage rates. Additionally, it highlights the significance of early detection, management of associated risk factors, and the impact of environmental and lifestyle factors on miscarriage. Future research directions include the development of targeted antioxidant therapies and their integration into standard prenatal care. This comprehensive approach aims to enhance understanding, prevention, and management of miscarriage, thereby improving maternal and fetal health outcomes. Keyword : This study examines the role of oxidative stress and its antagonists in miscarriage, highlighting the potential of antioxidants to improve pregnancy outcomes by mitigating oxidative damage. Highlights: Oxidative stress contributes to miscarriage by causing cellular damage and placental dysfunction. Antioxidants may help mitigate oxidative damage, improving pregnancy outcomes. Future research focuses on targeted antioxidant therapies in prenatal care. Keywords: oxidative stress, miscarriage, antioxidants, pregnancy outcomes, placental dysfunction